Evaluación de la incorporación de Omega-3 libre y nanoencapsulado en el desarrollo de un yogur - Diaz, Gabriela Esther (2023)
The health benefits derived from the consumption of omega-3 eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids have been strongly demonstrated in the scientific literature, and their consumption is recommended by health authorities throughout the world due to their influence on the prevention of chronic noncommunicable diseases. However, the highly reactive nature of EPA and DHA can compromise their integrity when used as bioactives in functional food design. Therefore, the present work proposes the nanoencapsulation of marine oil (rich in EPA and DHA) as a strategy to maintain its oxidative stability until the end of its useful life in yogurt on a laboratory scale. This work reflects the positive effect provided by nanocapsules as protection from EPA and DHA, in addition to the fact that their use did not show differences in the physicochemical and microbiological parameters between yogurts enriched with EPA+DHA (free or nanocapsules) and controls.